Reduce equation to quadratic form

(X+1)(X+2)(X+3)(X+4)=120 (X+1)(X+2)(X+3)(X+4)=120 ,

How to bring this equation to the form of ax2+bx+c=0 ax^{2} +bx+c=0

#Algebra #Math

Note by Joshi Rishit
7 years, 10 months ago

No vote yet
3 votes

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

You can always start by multiplying all the terms, but it will get really messy!

Here's a good way. Rearrange the terms like this:

(X+1)(X+4)(X+2)(X+3)=120(X+1)(X+4)(X+2)(X+3)=120

And multiply two terms at a time:

(X2+5X+4)(X2+5X+6)=120(X^2+5X+4)(X^2+5X+6)=120

Let x=X2+5X+4x=X^2+5X+4.

Now we have something like this:

x(x+2)=120x(x+2)=120

or x2+2x120=0x^2+2x-120=0.

Notice that this equation is in the form ax2+bx+c=0ax^2+bx+c=0 where a=1a=1, b=2b=2 and c=120c=-120. So we're done!

Hope this helps!

Mursalin Habib - 7 years, 10 months ago

Log in to reply

no sorry brother ans is not comin any way thanx for ur help

JOSHI RISHIT - 7 years, 10 months ago

Log in to reply

Continuing where Mursalin left:

after you got x2+2x120=0x^{2}+2x-120=0 solve it as x2+12x10x120=0x^{2}+12x-10x-120=0 => x(x+12)10(x+12)=0x(x+12)-10(x+12)=0 =>(x+12)(x10)=0(x+12)(x-10)=0 which gives x=10,12x=10,-12

for x=10,X2+5X+4=10=>X2+5X6=0=>X2+6XX6=0x=10, X^{2}+5X+4=10 => X^{2}+5X-6=0 => X^{2}+6X-X-6=0 =>X(X+6)(X+6)=0=>(X+6)(X1)=0=> X(X+6)-(X+6)=0 => (X+6)(X-1)=0 which gives X=1,6X=1,-6

for x=12,X2+5X+4=12=>X2+5X+16=0x=-12, X^{2}+5X+4=-12 => X^{2}+5X+16=0 which does not have any real roots since b24acb^{2}-4ac i.e., 2564<025-64 <0

so the answers are 1 and -6.

Swaraj Yadav - 7 years, 10 months ago

Log in to reply

@Swaraj Yadav Thanx very much bro

JOSHI RISHIT - 7 years, 10 months ago

you mean to say that arrange in such a way that the the sum of constants i.e 1,4 & 2,3 are same i.e. 5 lemme try.....

Vivek Sahu - 7 years, 10 months ago
×

Problem Loading...

Note Loading...

Set Loading...